El entorno familiar y su relación con el comportamiento de los niños y niñas de primer grado de educación básica de la escuela María Paulina Solís del cantón Yanzatza, provincia de Zamora Chinchipe, período 2013-2014 - Amaya Morocho, Maribi Belen (2014)
This thesis refers to "FAMILY ENVIRONMENT AND ITS RELATIONSHIP WITH THE BASIC EDUCATION FIRST GRADE CHILDREN BEHAVIOR "MARÍA PAULINA SOLÍS" CHILD CENTER YANZATZA CITY. 2013 - 2014‖. ALTERNATIVE GUIDELINES. Made according to the provisions of the Regulation of Academic Board of the National University of Loja. The General objective was to: Sensitize parents about the importance of the Family Environment for First Grade Children. The methods used for the preparation of this research work were: Scientist, Inductive, Deductive, Descriptive, and Statistical Model, which served to help efficiently achieve the goal. The techniques and instruments used were: Survey targeting parents or relatives of children in Basic Education First Grade ―Ralph Waldo Emerson " Children`s Center of Quito city, in order to establish the Family Environment and an Observing Guide applied to children`s Center. According to results of the survey of parents reveals that: 57% of respondents Parents value their Family environment as stable and 43% unstable. As seen in their homes all the features of family stability as adaptability, flexibility , bonding , affection, communication , norms and standards for each of its members are established taking into account their characteristics and needs. Analyzed the results of the Observation Guide is concluded that: 61% of boys and girls have investigated a Little Aggressive behavior Aggressive 28% , and 11% Very Aggressive . 51% of boys and girls have investigated behavior Shortly Passive Passive 40% , and 9% Very liabilities . 53% of boys and girls have investigated Assertive behavior, 38% Very Assertive, and 9% few Assertive.